Tipologi Daerah berdasarkan Indikator Pembangunan Berkelanjutan - Susyanto Tunut; Ketut Sukiyono; Retno Agustina Ekaputri (Journal of Management and Bussines (JOMB), 2022)
This study aims to evaluate regional typologies based on sustainable development indicators. This research method is descriptive quantitative. The research was carried out from June 020 to May 021 and used data for 019. The research area covers all regencies and cities in the province of South Sumatra. This research is a multi-correlation study of social, economic, environmental and institutional aspects which are indicators of sustainable development. Data analysis used Multivariate Analysis of Varians (Manova) and Rapid analysis for fisheries (Rapfish). The results of the study show that there are 4 cities with high sustainable development achievements and the remainder is moderate. It is necessary to increase the program to improve the achievement indicators of each indicator, namely social, economic, environmental and institutional. Keywords: Regional Expansion, South Sumatra, Sustainable Development Goals